USE OF INNOVATIVE TECHNOLOGIES IN THE DEVELOPMENT OF SPECIALIZED SKILLS IN BOXERS - Gapparov Zakhid Gapparovych (Journals Park Publishing, 2024)
In this article, the author tried to shed light on the psychological features of feeling the gap in boxers through a new methodology. The author tried to explain the elements of feeling of distance in boxers using a device that allows measuring nine types of distance in boxers.
Keywords: boxer, interval, distance, competition, psychological characteristics, device, result, technique, tactics, skill.